PENGARUH RASIO PENDAPATAN ASLI DAERAH TERHADAP KINERJA KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN DAN KOTA DI PROVINSI SUMATERA BARAT TAHUN 2017-2020 - Fitri Ramadhani; Lili Wahyuni; Witra Maison (Journal of Innovation Research and Knowledge, 2022)
This study aims to determine the effect of the ratio of regional taxes, the ratio of regional levies, the ratio of the results of separated regional wealth management, the ratio of other legitimate regional revenues on the financial performance of the regional government. The sample used is 19 districts/cities in West Sumatra Province in 2017-2020. The sampling technique used was total sampling. The type of data used is secondary data in the form of financial reports obtained from Http://sumbar.bps.go.id. The analysis used includes normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, r-square coefficient of determination and hypothesis testing.The results showed that each of the variables of the Regional Tax Ratio, Regional Retribution Ratio, Separate Ratio of Regional Wealth Management Results, Other Legitimate Regional Original Income Ratios affect the Financial Performance of Regional Governments, as well as simultaneously Regional Tax Ratios, Regional Levies Ratio , Ratio of Results of Separated Regional Wealth Management and Other Ratios of Legitimate Regional Original Income affect the Financial Performance of Regional Governments